Chimeric Antigens Receptor T Cell Therapy Improve the Prognosis of Pediatric Acute Lymphoblastic Leukemia With Persistent/Recurrent Minimal Residual Disease in First Complete Remission - Hu, Guan-hua; Cheng, Yi-fei; Zuo, Ying-xi; Chang, Ying-jun; Suo, Pan; Wu, Jun; Jia, Yue-ping; Lu, Ai-dong; Li, Ying-chun; Wang, Yu; Jiao, Shun-chang; Zhang, Long-ji; et al. (Frontiers in Immunology, 2022)
Background The presence of minimal residual disease (MRD) is an independent risk factor for poor prognosis in patients with acute lymphoblastic leukemia (ALL). Moreover, the role of chimeric antigen receptor T-cell (CAR-T) therapy in patients with MRD is currently unclear. Methods We conducted a prospective study to investigate the role of CAR-T therapy in patients with persistent/recurrent MRD-positive ALL in first remission. Results A total of 77 patients who had persistent/recurrent MRD were included. Of these patients, 43 were enrolled in the CAR-T group, 20 received chemotherapy as a bridge to allogeneic hematopoietic cell transplantation (allo-HSCT), and 14 patients received intensified chemotherapy. MRD negativity was achieved in 90.7% of the patients after CAR-T infusion. Patients who received CAR-T therapy had a higher 3-year leukemia-free survival (LFS) than patients who did not (77.8% vs. 51.1%, P = 0.033). Furthermore, patients in the CAR-T group had a higher 3-year LFS than those in the chemotherapy bridge-to-allo-HSCT group (77.8% [95% CI, 64.8–90.7%] vs. 68.7% [95% CI, 47.7–89.6%], P = 0.575) and had a significantly higher 3-year LFS than those in the intensified chemotherapy group (77.8% [95% CI, 64.8–90.7%] vs. 28.6% [95% CI, 4.9–52.3%], P = 0.001). Among the patients who received CAR-T therapy, eight were not bridged to allo-HSCT, and six (75%) remained in remission with a median follow-up of 23.0 months after CAR-T infusion. Conclusions Our findings show that CAR-T therapy can effectively eliminate MRD and improve survival in patients with a suboptimal MRD response.